The development and initial psychometric validation of the eHealth readiness scale. (December 2016) - Bhalla, Arjun; Durham, Robert L.; Al-Tabaa, Nadia; Yeager, Carolyn
Abstract: Participant attrition and non-adherence are common issues within eHealth interventions. There is need for a better understanding of who has interest in using these technologies. The current study developed and psychometrically evaluated the eHealth Readiness scale, which assesses user preparedness to engage in eHealth interventions. Construction of scale items was informed by the theory of self-efficacy, as well as the eHealth and eLearning literature. An initial validation was conducted with an undergraduate sample ( N = 195, Aged 18–51, M = 21.53, SD = 5.16). Continued validation of the scale was done with a sample of military mental health providers ( N = 64, Aged 29–80, M = 49.30, SD = 11.97) in a randomized controlled trial for an eHealth intervention. Results illustrated that scale items demonstrated good internal reliability (Cronbach's α = . 81 and 0.83), and a stable one-factor solution. Results also established construct validity for the scale. Results of an independent samples t -test indicated no significant difference in eHealth readiness scores between those who did and did not engage with the eHealth intervention, but scores for those who engaged were marginally higher. Current findings provide preliminary support for the psychometric properties of the eHealth readiness scale. Highlights: Scale was developed to assess preparedness to engage with eHealth interventions. Results provide initial support for our scale as a brief, reliable and valid tool. Future study should substantiate the scale as a screening tool and factor structure.